2017
DOI: 10.1038/srep38563
|View full text |Cite
|
Sign up to set email alerts
|

Tubules of plant reoviruses exploit tropomodulin to regulate actin-based tubule motility in insect vector

Abstract: Plant reoviruses are known to exploit virion-packaging tubules formed by virus-encoding non-structural proteins for viral spread in insect vectors. Tubules are propelled by actin-based tubule motility (ABTM) to overcome membrane or tissue barriers in insect vectors. To further understand which insect factors mediate ABTM, we utilized yeast two-hybrid and bimolecular fluorescence complementation assays to test interactions between tubule protein Pns10 of rice dwarf virus (RDV), a plant reovirus, and proteins of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…The investigation on the regulators of ABTM is beneficial for the improved understanding of the mechanism of ABTM. Our previous study revealed that Tmod, a positive regulator of RDV ABTM, functioned in viral infection by directly interacting with tubule protein Pns10 (Chen et al 2017). Because Tmod could control the length and stability of the actin-tropomyosin filament, Pns10 utilizes Tmod to elongate the Pns10 tubules to accomplish ABTM (Chen et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The investigation on the regulators of ABTM is beneficial for the improved understanding of the mechanism of ABTM. Our previous study revealed that Tmod, a positive regulator of RDV ABTM, functioned in viral infection by directly interacting with tubule protein Pns10 (Chen et al 2017). Because Tmod could control the length and stability of the actin-tropomyosin filament, Pns10 utilizes Tmod to elongate the Pns10 tubules to accomplish ABTM (Chen et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…During the process of ABTM, actin-associated proteins, including myosin, profilin, and cofilin, also positively participate in tubule formation or actin engine regulation (Wei et al 2008;Liu et al 2011;Chen et al 2012;Jia et al 2014;Mar et al 2014). In our previous publication, we showed that tropomodulin (Tmod), an actin-associated protein controlling the length and dynamics of the actin-tropomyosin filament, positively regulates RDV Pns10 tubule trafficking via the direct interaction with Pns10 (Chen et al 2017). This interaction promotes viral infection (Chen et al 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many intracellular pathogens, including viruses, parasites, and bacteria, invade, traffic within, and exit their target cells in a cytoskeleton‐dependent manner (Greber & Way, ; Gruenheid & Finlay, ). Recently, a model of actin‐based tubule motility for the spread of rice virus including RDV in insect vector has been proposed (Chen et al., ; Jia et al., ; Liao et al., ; Mao et al., ; Wei & Li, ). In this model, a direct interaction of tubule composed of RDV Pns10 , RGDV Pns11 , or SRBSDV P7‐1 protein with cellular skeleton components (actin, myosin, profilin, gelsolin, cofilin, and tropomodulin) was observed; these components formed a “lighted rocket” to propel the tubule to break through the membrane or tissue barriers for spread and transmission in insect vectors.…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione S‐transferase (GST) pull‐down assay was conducted as Chen's and Liao's method (Chen, Wang, Ren, Xie, & Wei, ; Chen, Zhang, Zhang, Mao, & Wei, ; Liao et al., ). In brief, RDV Pns10 and Nc‐TnC genes were cloned into pGEX‐3X and pDEST‐17 to construct plasmids expressing GST and 6 × His fusion protein, respectively, with the primers of Pns103 ‐F/R and TnC5 ‐F/R (Table ).…”
Section: Methodsmentioning
confidence: 99%